A comparative study of pulse oximetry with the conventional pulp testing methods to assess vitality in immature and mature permanent maxillary incisors - Shini Susan Samuel; Abi M Thomas; Namita Singh (Wolters Kluwer Medknow Publications, 2014)
Context: Subjective pulp tests are not reliable, particularly in children. It is important for dentists to understand the various pulp testing methods that are available in order to make an accurate diagnosis of the state of dental pulp in children. Aims: To assess pulp vitality and compare the reliability of pulse oximetry with the conventional pulp tests (electric pulp test and cold test) in immature and mature permanent maxillary incisors. Subjects and Methods: Sixty selected children aged 7-18 years with normal permanent maxillary central and lateral incisors were categorized into Group I (mature teeth) and Group II (immature teeth). Thirty endodontically treated permanent maxillary incisors were used as the negative control. Statistical Analysis Used: The sensitivity, specificity, positive predictive value, and negative predictive value were calculated and the results were analyzed. Results: The specificity for the pulse oximetry test, cold test, and electric pulp test in Group I (mature teeth) was 100%. The specificity for the pulse oximetry and cold test in Group II was 100% and 80% for electric pulp test. Conclusions: For an accurate pulpal diagnosis in children, one should not rely on one pulp test alone. In young children, pulse oximetry method was found to be as accurate as cold test but large variations were seen in electric pulp test.